O desenvolvimento da análise financeira nos últimos anos - Oliveira, Arnaldo Prestes (1982)
The Financial Rate Analisis has been, widely, used since the end o f the last century, in the evaluation of financial demonstrative, however it lost credit by the 60's. Then,by this time, Beaver based on the existing literature tests empirically many asst.unptions considered as true and getaudi fferent results, for this he used the univariate statistical methodology, that is, analized the rate one by one. Altman contest the methodology used by Beaver and makes a model using multivariate statistics that is, severa! rates are studied, establishing a score limit. Other authors, based in these two studies, now criticizing, then comparing, make other models, then we have: Deakin, Blum, Libby, Kennedy, Kanitz, Zappa, Collongues, Conan, Holder, C.E.S.A. and others that were not mentioned in this study. This study showed the study of each one of the author individualy and in a second moment presented. Criticismand comparisons these models had, trying to make clear these criticisms and comparisons served to encourage the development of the Financial Analisis, to a point that one can name Altman, who dug to criticisms anel, his interest inbringing da ta to date, reorganize his original model (1968), making the Zeta model (1977). The secon concern of this study was to make clear some points that could be taken from the avaiagle material, thus we tried to answer wnich rates were used by the models and as a conclusion, we got at the evidence that there aren't few rates that best discriminate a bankrupt and non-bankrupt firm. A nother question was, if these models served for all the types and sizes of firms and we got at a conclusion they serve, aslong as the analyst adapt their particular necessities. And finally we tried to check what purposes these models could corresporld to and so, we pointed the comercial credit analisis, for invetment, internal decisions, stock purchases and sales, etc. We conclude, that the various models developad in the se last years, really brought progress to financial analisis, but these results must be carefully adapted to several situations and moreover, due to the development of other sciences may add efforts with the purpose of reaching a larger development.